Effects of Municipal Abattoir Waste on Water Quality of Woji River in Trans-Amadi Industrial Area of Port Harcourt, Nigeria: Implication for Sustainable Urban Environmental Management - Wizor, Collins H; Nwankwoala, Hycienth O (International Journal of Geography and Geology, 2019)
This research provides a spatial analytical framework for sustainable urban environmental management. It examines the effects of abattoir wastes on water quality of the Woji River in the Trans-Amadi industrial area of Port Harcourt, Nigeria. The research was premised on the fact that untreated wastes from the Trans-Amadi abattoir are discharged directly into open drainage which flows into the river. Water samples were collected from nine points along the stream (upstream; 3 samples, downstream; 3 samples, fallout; 3 samples) and subjected to physico-chemical laboratory analysis for total dissolved solids (TDS), temperature, pH, turbidity, hardness, iron content, nitrate, sulphate, magnesium, nickel, copper as well as some biological parameters. The results obtained from these parameters were at variance with the allowable limits of WHO standards for human use and aquatic life. The result further showed that the abattoir effluent has lowered the quality of the receiving Woji River particularly at fallout point and downstream. There is, therefore, need to stop the discharge of effluents into the receiving Woji River by upgrading the wastewater and urban waste management techniques of the abattoir to international standard.